Antimicrobial Susceptibility Pattern of Acinetobacter calcoaceticus-Acinetobacter baumannii Complex Isolated from Sputum in a Tertiary Care Hospital - Sapkota, Jyotshna; Sharma, Manisha; Shrestha, Deepti; Jha, Beena (Journal of Institute of Medicine Nepal, 2019)
Introduction Acinetobacter calcoaceticus-Acinetobacter baumanni (ACB) complex is one of the commonest cause of hospital acquired and ventilator associated pneumonia. Multidrug resistant Acinetobacter species have become a matter of huge concern. This study was done to find out the antibiotic susceptibility pattern of Acinetobacter calcoaceticus-Acinetobacter baumanii complex from sputum samples. Methods This descriptive cross-sectional study was carried out in Clinical Microbiology laboratory from July 2018 to Jan 2019 after ethical approval. Acinetobacter calcoaceticus-Acinetobacter baumannii complex was identified on the basis of its microscopy and morphological characteristics followed by biochemical tests. Antibiotic sensitivity test of isolated pathogens was done using Muller Hinton Agar by Kirby-Bauer method. Results Of the 384 culture positive sputum specimen, 76 (19.80%) were Acinetobacter calcoaceticus-Acinetobacter baumannii complex. Most of the isolates were resistant to commonly used antibiotics, 72.36% of the isolates were multidrug resistance and 3.95% isolates were resistant to tigecycline. Conclusion This study provides valuable information regarding prevalence of Acinetobacter calcoaceticus-Acinetobacter baumannii complex from sputum specimen. The alarming number of Multidrug resistance isolates is worrisome finding. Antibiotics like Tigecycline and Colistin which is still sensitive to isolates should be cautiously used only in MDR cases.